Determinant of happiness among urban civil servants of Universiti Teknologi MARA, Shah Alam - Mohamed Harith, Nor Hafizah; Md. Noon, Hazizan (Faculty of Administrative Science and Policy Studies, Universiti Teknologi MARA (UiTM), Malaysia, 2016)
Since independence in 1957, Malaysia has initiated vigorous socio-economic and other developmental projects in order to raise the well-being and the quality of life of its people. The present study aimed to reveal insights on the reality of life satisfaction among the urban dwellers in Malaysia, particularly the urban civil servants who lived in the major cities in Klang Valley. Adopting the Allardt’s dimensions of welfare, this study explored the subjective meaning of life satisfaction among the administrative staff of a Malaysian university namely Universiti Teknologi MARA (UiTM). Sixteen key informants from four different categories of administrative staff of the University’s main campus in Shah Alam, Selangor were engaged in the researchers’ in-depth interviews whose inputs were later reinforced and verified through written feedback survey. The NVivo version 9 was employed to analyse the data and the main finding has shown that the responses centered around